2015
DOI: 10.1089/vim.2014.0121
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the Immunogenicity of Porcine Circovirus Type 2 DNA Vaccine by Recombinant ORF2 Gene and CpG Motifs

Abstract: Nowadays, adjuvant is still important for boosting immunity and improving resistance in animals. In order to boost the immunity of porcine circovirus type 2 (PCV2) DNA vaccine, CpG motifs were inserted. In this study, the dose-effect was studied, and the immunity of PCV2 DNA vaccines by recombinant open reading frame 2 (ORF2) gene and CpG motifs was evaluated. Three-week-old Changbai piglets were inoculated intramuscularly with 200 μg, 400 μg, and 800 μg DNA vaccines containing 14 and 18 CpG motifs, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Our previous research demonstrated that CpG motifs as an adjuvant could boost the humoral and cellular immunity of pigs to against PCV2, especially in terms of cellular immunity [10]. This study evaluated the adjuvant of CpG motifs to PCV2 DNA vaccine and mainly detected the serum antibody levels in mice by ELISA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous research demonstrated that CpG motifs as an adjuvant could boost the humoral and cellular immunity of pigs to against PCV2, especially in terms of cellular immunity [10]. This study evaluated the adjuvant of CpG motifs to PCV2 DNA vaccine and mainly detected the serum antibody levels in mice by ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…The current research on CpG as immune adjuvant was mainly focused on the mouse and human disease. Based on the earlier research in the authors ‘laboratory (Cheng KH, “Study on Series of DNA Vaccines Against Porcine Circovirus Type 2[D],”[master’s thesis QingDao Agricultural University, 2009]), we first reported the CpG motifs as an adjuvant insert to the PCV2 DNA vaccine that could boost immunity in pigs [10]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CpG motifs have been encoded within plasmid DNA vaccines [ 108 , 109 ], or co-delivered with DNA vaccines on either other DNA vectors [ 110 ] or oligonucleotides (reviewed in [ 111 , 112 ]). Miniplasmid vectors have demonstrated utility as improved DNA vaccines [ 37 , 38 , 39 ].…”
Section: Development Of Minicircles and Minivectorsmentioning
confidence: 99%
“…Binding of unmethylated CpG DNA to TLR9 results in the release of type I IFNs and in some contexts proinflammatory cytokines (Sasai et al,2010; Wagner, 2004). Studies examining the role of TLR9 signaling in DNA vaccine immunogenicity suggested that it may play a role in the enhancement of adaptive immune responses, but is not necessary for their induction (Babiuk et al, 2004; Chen et al, 2015; Li et al, 2015; Mitsui et al, 2009; Schneeberger et al, 2004; Stan et al, 2001). In our own preclinical and clinical studies with DNA vaccines encoding tumor antigens, we have enhanced TLR9 signaling by using a plasmid vector (pTVG4) whose backbone was modified to contain CpG-rich sequences (Becker et al, 2010a; McNeel et al, 2009a; Rekoske et al, 2015; Smith & McNeel, 2011).…”
Section: Dna Vaccines – Mechanisms Of Action; Increasing Immunogenmentioning
confidence: 99%